Empa's New Clothes: The Untold Story of the Empa-Reg Outcome Trial - Alzaid, Aus (Diabetes Technol Ther, 2017)
It is no secret that the diabetes community has been yearning for good news for quite some time. One outstanding issue undermining effective diabetes management has been the lack of demonstrable effects of glycemic interventions on cardiovascular (CV) outcome in people with type 2 diabetes. This, however, seems to have changed recently after the publication of the Empa-Reg Outcome Trial. The study reported an impressive reduction in CV deaths that was observed within weeks of treatment with the diabetes agent, Empagliflozin. The results exceeded all expectations and was quickly embraced by a wide and receptive diabetes audience. Fans and admirers of the study have since set out to accommodate the new findings to reshape our diabetes practice guidelines. However, before everything becomes cast in stone, I believe there's another side to the story of the Empa-Reg Outcome trial that the diabetes community needs to hear. Here, I debate the merits of the study and present the case as to why I think we might be led down the garden path by accepting this study at mere face value.